Comparison of Renal Safety of Tenofovir and Telbivudine in Chronic Hepatitis B Patients: A Real World Study in Indonesia - Gani, Rino Alvani (UI Scholars Hub, 2018)
Introduction. Tenofovir disoproxil fumarate (tenofovir) and telbivudine are two available nucleos(t)ide analogue (NA) for the treatment of chronic hepatitis B (CHB) patients. Tenofovir has been known as a nephrotoxic agent in HIV patients, but still controversy in CHB patients. On the other hand, telbivudine had a renal protective effect and increased estimated glomerular filtration rate (eGFR). This studi aimed to address the renal safety of tenofovir and telbivudine in Indonesian patients. Method. A retrospective cohort study design was conducted in CHB patients who prescribed with tenofovir or telbivudine from January 2013 to December 2016. Patients who hade baseline eGFR